Randomised sham-controlled double-blind trial evaluating remote ischaemic preconditioning in solid organ transplantation: a study protocol for the RIPTRANS trial. Issue 11 (16th November 2020) - Uutela, Aki; Helanterä, Ilkka; Lemström, Karl; Passov, Arie; Syrjälä, Simo; Åberg, Fredrik; Mäkisalo, Heikki; Nordin, Arno; Lempinen, Marko; Sallinen, Ville
Abstract : Introduction: Remote ischaemic preconditioning (RIPC) using a non-invasive pneumatic tourniquet is a potential method for reducing ischaemia-reperfusion injury. RIPC has been extensively studied in animal models and cardiac surgery, but scarcely in solid organ transplantation. RIPC could be an inexpensive and simple method to improve function of transplanted organs. Accordingly, we aim to study whether RIPC performed in brain-dead organ donors improves function and longevity of transplanted organs. Methods and analyses: RIPTRANS is a multicentre, sham-controlled, parallel group, randomised superiority trial comparing RIPC intervention versus sham-intervention in brain-dead organ donors scheduled to donate at least one kidney. Recipients of the organs (kidney, liver, pancreas, heart, lungs) from a randomised donor will be included provided that they give written informed consent. The RIPC intervention is performed by inflating a thigh tourniquet to 300 mm Hg 4 times for 5 min. The intervention is done two times: first right after the declaration of brain death and second immediately before transferring the donor to the operating theatre. The sham group receives the tourniquet, but it is not inflated. The primary endpoint is delayed graft function (DGF) in kidney allografts. Secondary endpoints include short-term functional outcomes of transplanted organs, rejections and graft survival in various time points up to 20 years. We aim to show that RIPC reduces the incidence of DGF from 25% to 15%. According to this, the sample size is set to 500 kidney transplant recipients. Ethics and dissemination: This study has been approved by Helsinki University Hospital Ethics Committee and Helsinki University Hospital's Institutional Review Board. The study protocol was be presented at the European Society of Organ Transplantation congress in Copenhagen 14−15 September 2019. The study results will be submitted to an international peer-reviewed scientific journal for publication. Trial registration number: NCT03855722 .